Computational Design, Synthesis and Evaluation of Caffeine Imprinted Molecular Imprint Polymer (MIP) - Mohamad Badrul Hisam Salleh (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Caffeic acid (CA) is a naturally occurring organic compound found in various plants such as pear, apple, and basil. It also has been identified as one of the active antioxidant essential in preventing diseases such as cancer and coronaries. Caffeic acid which has the medicinal value needs to be isolated from plants by using method of molecular imprinting polymer (MIP). MIP can be described as a way of making artificial locks for molecular keys which include the concept of preparing substrate-selective recognition sites in a matrix by using a molecular template. In this research, the approach of computer aided design of MIP for caffeic acid by molecular modeling approach was done to get the optimum procedure in MIPs synthesis. The modelling is done to select monomer that is usable to bind several active sites in caffeic acid. Molecular modeling is performed using semi-empirical Austin Method (AM1) to study the interaction between caffeic acid as template and a functional monomer molecule. Based on the result obtained from the modelling data, ratio of 1:4, 1:4.5, 1:5, 1:5.5 and 1:6 of functional monomer over template were expected to have good binding capabilities to be synthesized. The rebinding assay of the synthesized polymer showed that the ratio of 1:5.5 having high binding selectivity with 81% of caffeic acid absorbed inside the polymer.